Working with the patient and clinical community to deliver clinical research in cystic fibrosis. James Lind CF Phase II - Smith, S.J.; Rowbotham, Nicola J.; Smyth, Alan R. (Cystic Fibrosis Trust, 2018)
This is a protocol which sets out the aims, objectives and commitments of the second phase of the James Lind Alliance Priority Setting Partnership in Cystic Fibrosis and the basic roles and responsibilities of the partners therein. The James Lind Alliance Priority Setting Partnership in cystic fibrosis was carried out in 2016 using a robust and widely accepted methodology to develop the top 10 questions for clinical research in CF, through discussions with both the clinical and patient community. We now aim to explore four of the top ten questions from this process and develop them into a series of testable hypotheses for clinical research. Where the hypothesis will be tested in a clinical trial, we will develop a PICO question for each hypothesis (Population, Intervention, Comparator & Outcome). We will use online surveys and focus groups to achieve our aim.